Efficiency of Intranasal Fentanyl in Patients with Breakthrough Cancer Pain in Daily Practice - Results of the German Non-Interventional Study with Instanyl® (GENISIS) - Michael A Ueberall; Bernd-Oliver Maier; Thomas Nolte (Global Journal of Anesthesiology - Peertechz Publications, 2014)
Objective: Breakthrough cancer pain (BTcP) affects 19-95% of cancer patients (dependent on the definition and methods used and the populations studied) and is associated with detrimental physical, psychological and social complications in affected individuals as well as with significant economic burden on society and the healthcare system. This study evaluated the analgesic efficacy and safety of intranasal fentanyl spray (INFS) for the treatment of BTcP in a clinical setting with a special focus on its impact on health care resource utilization. Research design and methods: This was a prospective, open-label, noninterventional, multi-center study. Opioid-tolerant adult patients with BTcP received INFS in the course of routine clinical practice, and  completed standardized questionnaires as well as BTcP diaries over a 28-day observation period. Clinical trial registration: ClinicalTrials.gov Identifier: NCT00994760 Main outcome measures: Efficacy was assessed using measures of BTcP intensities, the times to first and to the maximum effect of INFS, as well as changes in BTcP-related restrictions in quality-of-life (QoL), activities of daily life (ADL) and overall wellbeing. Further analyses based on INFS-related changes in health care resource utilization. Treatment emergent adverse events (TEAEs) were recorded throughout.  Results: Overall, 58 centers participated and enrolled 131 patients, of whom 116 (88.5%) completed the observation period and documented a total of 556BTcP episodes. The 100μg dose was judged as the most effective INFS dose in 64.0a% of patients, followed by 50 μg (28.0a%) and 200 μg (8.0 a%). The study recorded a substantial INFSrelated improvement in maximum BTcP intensity, compared with baseline as well as prior use. Patients reported experiencing the first effects of the study drug within 5 minutes of administration in 81.9% of episodes, and a time to maximum effect within 10 minutes in 81.4% of episodes. QoL and BTcP-related restrictions in ADL showed considerable improvements during the observation period. INFS was well tolerated, with sixpatients (4.6%) experiencing ≥1 study drug-related adverse event. Study limitations include a modest size and duration, and the single-arm design. Conclusion: Under the conditions of this non-interventional open-label study, INFS proved to be a rapid onset, highly effective and well tolerated alternative for the treatment of BTcP in opioid-tolerant cancer patients. INFS treatment was not only associated with substantial improvements in BTcP intensity as well as related restrictions in QoL and ADL, but also with a respectable decrease of health care resource demands - especially in the field of ambulatory palliative care nursing services.